Employee's attitude and managerial support on lean benefits - Sivaprakash Vatumalai, 1988-; Norhani Bakri, 1961-, supervisor; Fakulti Pengurusan (2015)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2015